Synthesis, XRD, HAS, in silico molecular docking studies and biological assessment of novel Schiff base compounds as anti-cancer and antimicrobial agents. Issue 1 (1st January 2020) - Said, Musa A.; Al-Harbi, Wael S.; Shanmugam, Mani; Aljohani, Faizah S.; Bouqellah, Nahla A.; Al-Kaff, Nadia S.
Abstract : In this study, versatile multifunctional Schiff base (SB) derivatives were synthesized. Compounds 1–8 were prepared by a mild condition and were pharmacologically assessed for their role in vitro anti-cancer and their impact on human fibrosarcoma (HT-1080) and cervical cancer cells (HeLa), in addition to their antimicrobial activity regarding fungal strains, gram-positive and gram-negative bacteria. Preliminary in silico study of 1–8 and the standard compound (5-Fluorouracil) was accomplished, using Drug2Way and PASS software. Besides, docking investigations were carried out using Schrödinger software to determine the interaction of p53-MDM2 and pf-DHFR binding affinity for all the compounds. The antimicrobial results exhibited that these novel compounds have modest to good inhibitory action against the tried bacterial and fungal strains. The crystal structures of 2 and 7 have been determined. Hirshfeld Surface Analysis (HSA) is in agreement with the XRD studies. Both compounds have shown enol–imine tautomeric forms as EE isomer.